Sport-specific conditioning variables predict offensive and defensive performance in high-level youth water polo athletes - Sekulic, D.; Kontic, D.; Esco, M. R.; Zenic, N.; Milanovic, Z.; Zvan, M. (The Journal of Strength and Conditioning Research, 2016)
Specific-conditioning capacities (SCC) are known to be generally important in water polo (WP), yet the independent associations to offensive and defensive performance is unknown. This study aimed to determine whether offense and defense abilities in WP were independently associated with SCC and anthropometrics. The participants were 82 high-level male youth WP players (all 17-19 years of age; body height, 186.3 ± 6.07 cm; body mass, 84.8 ± 9.6 kg). The independent variables were body height and body mass, and 5 sport-specific fitness tests: sprint swimming over 15 meters; 4 × 50-meter anaerobic-endurance test; vertical in-water-jump; maximum intensity isometric force in upright swimming using an eggbeater kick; and test of throwing velocity. The 6 dependent variables comprised parameters of defensive and offensive performance, such as polyvalence, i.e., ability to play on different positions in defensive tasks (PD) and offensive tasks (PO), efficacy in primary playing position in defensive (ED) and offensive (EO) tasks, and agility in defensive (AD) and offensive (AO) tasks. Analyses showed appropriate reliability for independent (intraclass coefficient of 0.82-0.91) and dependent variables (Cronbach alpha of 0.81-0.95). Multiple regressions were significant for ED (R2 = 0.25; p < 0.01), EO (R2 = 0.21; p < 0.01), AD (R2 = 0.40; p < 0.01), and AO (R2 = 0.35; p < 0.01). Anaerobic-swimming performance was positively related to AD (ß = -0.26; p = 0.05), whereas advanced sprint swimming was related to better AO (ß = -0.38; p = 0.05). In-water-jumping performance held the significant positive relationship to EO (ß = 0.31; p = 0.05), ED (ß = 0.33; p = 0.05), and AD (ß = 0.37; p = 0.05). Strength and conditioning professionals working in WP should be aware of established importance of SCC in performing unique duties in WP. The SCC should be specifically developed to meet the needs of offensive and defensive performance in young WP athletes.